The livery collar: politics and identity in fifteenth-century England - Ward, Matthew (2014)
This study examines the social, cultural and political significance and utility of the livery collar during the fifteenth century, in particular 1450 to 1500, the period associated with the Wars of the Roses in England. References to the item abound in government records, in contemporary chronicles and gentry correspondence, in illuminated manuscripts and, not least, on church monuments. From the fifteenth century the collar was regarded as a potent symbol of royal power and dignity, the artefact associating the recipient with the king. The thesis argues that the collar was a significant aspect of late-medieval visual and material culture, and played a significant function in the construction and articulation of political and other group identities during the period. The thesis seeks to draw out the nuances involved in this process. It explores the not infrequently juxtaposed motives which lay behind the king distributing livery collars, and the motives behind recipients choosing to depict them on their church monuments, and proposes that its interpretation as a symbol of political or dynastic conviction should be re-appraised. After addressing the principal functions and meanings bestowed on the collar, the thesis moves on to examine the item in its various political contexts. It then places the collar within the sphere of medieval identity construction. In the final two chapters collars on church monuments are used as a starting point for conducting prosopographical studies of groups of linked individuals, in order to explore political and other types of shared identities at both a national and local level. It is argued that livery collars were used on church monuments as a manifestation, and indeed perpetuation, of the collective identity of the deceased and their kin. The inclusion of collars on church monuments could be used, as it were, differently, depending on local social, geographical and tenurial contexts. The author's original contribution to research centres on his findings regarding the nature of political affiliation and political life in the fifteenth century. In addition, the thesis offers a fresh methodology with which to analyse local history and networks. The collar is used as a vehicle through which to analyse and appraise wider themes of late-medieval politics and culture, and to explore the nature and understanding of royal power in the fifteenth century. Original conclusions are developed regarding the nature and extent of political thinking and conviction during the period - indeed the very meaning of politics to contemporaries at the centre and on the periphery of the polity - and its visual manifestation.